OUTCOME OF CHEMOTHERAPY IN NON ACUTE PROMYELOCYTIC ACUTE MYELOID LEUKAEMIA - Nighat Shahbaz; Parvez Ahmed; Tariq Mehmood Satti; Nadeem Paracha; Syed Kamran Mehmood; Qamar Un Nisa Chaudhary; Mehreen Ali Khan; Humayyun Satti (Pakistan Armed Forces Medical Journal, 2020)
Objective: Retrospective analysis to evaluate overall response and outcome of various therapeutic regimens given in patients with non acute promyelocytic acute myeloid leukaemia (non APL AML).